(untitled) (Comprehensive Journal of Science, 2026)
This study presents a numerical analysis of hydraulic flow characteristics within a centrifugal pump using Computational Fluid Dynamics (CFD) techniques via ANSYS Fluent. The research aims to investigate the correlation between pressure distribution and velocity fields under varying operating conditions to enhance performance and predict complex hydraulic phenomena. The methodology involved developing a high-fidelity 3D geometric model using SolidWorks, followed by an intensive meshing process comprising 850,038 cells to ensure solution accuracy and numerical stability. Pump performance was simulated at a rotational speed of 10,000 rpm under two boundary conditions: the first with an inlet velocity of 2 m/s and an outlet pressure of 25,000 Pa, and the second with an inlet velocity of 3 m/s and an outlet pressure of 30,000 Pa. The results demonstrate full consistency with fundamental physical principles, clearly capturing the conversion of kinetic energy into pressure as the fluid moves from the impeller eye to the volute casing. Furthermore, the study reveals that increasing flow velocity and discharge pressure significantly raises the maximum total pressure, while the peak velocity remains primarily governed by the rotational speed of the blades. The paper concludes that digital simulation provides a reliable tool for identifying hydraulic stress zones and mitigating cavitation risks during the early stages of design.